2014
DOI: 10.1186/s12983-014-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated adaptive evolution, episodic relaxation of selective constraints, and pseudogenization of umami and sweet taste genes TAS1Rs in catarrhine primates

Abstract: BackgroundUmami and sweet tastes are two important basic taste perceptions that allow animals to recognize diets with nutritious carbohydrates and proteins, respectively. Until recently, analyses of umami and sweet taste were performed on various domestic and wild animals. While most of these studies focused on the pseudogenization of taste genes, which occur mostly in carnivores and species with absolute feeding specialization, omnivores and herbivores were more or less neglected. Catarrhine primates are a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Sweet taste "blindness" observed in some carnivorous mammals, such as domestic cat, California sea lion, southern fur seal, Pacific harbor seal, Asian small-clawed otter, spotted hyena, fossa, banded linsang, bottlenose dolphin, and vampire bats, have been suggested to be the consequence of pseudogenization of T1R2 since they do not require the receptor for sweet food perception [6,7,10,11]. However, almost all omnivorous and herbivorous mammals with the habit to consume sugars have a functional T1R2 structure [6,7,10,[12][13][14][15]. Unlike pseudogenization of T1R2 in some carnivorous mammals, the evolution of sweet taste in birds is in absence of T1R2 despite food habits [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet taste "blindness" observed in some carnivorous mammals, such as domestic cat, California sea lion, southern fur seal, Pacific harbor seal, Asian small-clawed otter, spotted hyena, fossa, banded linsang, bottlenose dolphin, and vampire bats, have been suggested to be the consequence of pseudogenization of T1R2 since they do not require the receptor for sweet food perception [6,7,10,11]. However, almost all omnivorous and herbivorous mammals with the habit to consume sugars have a functional T1R2 structure [6,7,10,[12][13][14][15]. Unlike pseudogenization of T1R2 in some carnivorous mammals, the evolution of sweet taste in birds is in absence of T1R2 despite food habits [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these results suggested that the maltose response is related to both Tas1R2 and Tas1R3, indicating that the critical amino acids for binding are different from those for sucrose. In comparisons of Tas1R2 and Tas1R3 VFTD between Hominidae and Cercopithecinae, mutations at 45 and 43 amino acid residues have been observed, respectively13. We infer that these mutations affect sweet taste sensitivity to natural sugars by changing Tas1R2/Tas1R3 function.…”
Section: Discussionmentioning
confidence: 73%
“…Primate species have various mutations in Tas1R2 and Tas1R3 13. Generally, most sweet taste compounds bind to a huge external membrane domain called the venus flytrap domain (VFTD) of Tas1R214.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained TAS1R3 nucleotide sequences from Liu et al () and by searching for the gene name or BLASTing the human sequence against the NCBI and Ensembl databases (Supporting Information Table 1). Hence, we compiled all of the primate TAS1R sequences currently available via Genbank, genome browsers and short read archives.…”
Section: Methodsmentioning
confidence: 99%